Knowledge, Skills, and Self-Disclosure Following a Sexual Abuse Prevention Program Among Iranian Preschoolers: A Cluster Quasi-Experimental Controlled Study. Issue 9 (May 2023) - Maleki, Zohreh; Damghanian, Maryam; Rad, Maryam; Farnam, Farnaz
Standard empirical studies are needed despite three decades of research on child sexual abuse prevention programs (CSAPPs). This study aimed to investigate the effects of CSAPP on the child's sexual safety. A multicenter, random cluster, quasi-experimental controlled survey was conducted in a 1:1 ratio in Tehran, Iran, from May to December 2019 in seventy 5- to 6-years-old children from 10 kindergartens. In groups of 7 to 8, the intervention group participated in four sessions of 45 minutes of face-to-face sexual self-care training, 3 to 4 days apart. The control groups received one session on accident safety. Knowledge, self-protective skills, fear, and self-disclosure were assessed respectively by the "Personal Safety Questionnaire (PSQ), " "What If Situation Test (WIST), " "Fear Assessment Thermometer Scale (FATS), " and researcher-made questions before and 8 weeks after the intervention. At the baseline, children obtained 70% of knowledge and 45% of protective skills scores. After the intervention, knowledge, protective skills, and detection of "appropriate requests" were significantly promoted ( p  < .001). Detecting "inappropriate requests" did not differ; however, all quadruple skills (Say, Do, Tell, and Report) improved significantly. "Girl sex" and "parents' education" were related factors promoting children's protective skills. Sexual abuse self-disclosure was 4.2% ( n  = 3), and one child reported child sexual abuse (CSA) only after the intervention. Despite the lack of formal education, children's basic knowledge reflects the importance of parents in preventing CSA. However, the CSAPP significantly improved children's skills and revealed one CSA case. CSAPP should not focus solely on risky scenarios because if children cannot distinguish between safe and unsafe situations, they will experience unnecessary anxiety. Even after recognizing the dangerous conditions, CSA prevention will practically fail without appropriate reactions such as escaping and reporting. CSAPP should emphasize individual rights such as body ownership and assertiveness skills and explain the "danger of known people" with detailed scenarios, especially in collectivistic and traditional societies.